Exploring The Emerging Trends of Reusable Shipping Packaging for E-Commerce - Baskoro, Muhammad Lahandi (JISA(Jurnal Informatika dan Sains), 2020)
The rapid growth of e-commerce in terms of transaction volume and value has raised environmental concerns because of the potential for packaging waste it generates. Single-use shipping packages often result in piles of waste from cardboard, plastic and seal tape after the product is received by consumers. On the other hand, the customers of e-commerce products are also reported to be uncomfortable with shipping packaging which is often considered excessive. This problem gave birth to an innovative solution in the form of reusable shipping packaging for e-commerce product. This solution certainly considered interesting and promising, nevertheless, the scientific studies that address this issue are still limited. Therefore, this study aims to explore e-commerce shipping packaging, particularly in terms of its identifying attributes and seeking possible patterns. The findings are discussed using a descriptive analysis approach. As a result, it is found that several companies have launched products and services related to reusable e-commerce shipping packaging, and there are indications of certain patterns that are interrelated between these packaging attributes. This study hopes to contribute to the academic literature in the field of e-commerce reusable packaging, which is considered still in the infancy period.